Adaptive path selective linear muitipath-decorrelating receiver for CDMA frequency-selective fading channels - Ulusoy, AH; Amca, HA; Hacioglu, K; Rizaner, A (IEEE, 2000)
The Multipath-Decorrelating receiver performance depends on the number of resolvable paths. Tbe linear Multipath-Decorrelating receiver uses as many branches as the number of resolvable paths of the channel in order to improve the performance of the system. However, using all of the resolvable paths of the channel in the receiver increases the system complexity and the decorrelating: filter implemented by the use of all the resolvable paths produces high noise enhancement. In this paper, it is shown that taking a subset of the resolvable paths can reduce both system complexity and noise enhancement and improve system performance.
52nd IEEE Vehicular Technology Conference (VTC 2000) -- SEP 24-28, 2000 -- BOSTON, MA